eCM 2007
DOI: 10.22203/ecm.v013a06
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen, nitric oxide and articular cartilage

Abstract: Molecular oxygen is required for the production of nitric oxide (NO), a pro-inflammatory mediator that is associated with osteoarthritis and rheumatoid arthritis. To date there has been little consideration of the role of oxygen tension in the regulation of nitric oxide production associated with arthritis. Oxygen tension may be particularly relevant to articular cartilage since it is avascular and therefore exists at a reduced oxygen tension. The superficial zone exists at approximately 6% O 2 , while the dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(92 citation statements)
references
References 77 publications
5
81
0
6
Order By: Relevance
“…Thus, histopathlogical examination of the arthritic joints revealed that FG (1%) more markedly suppressed the articular lesions than ibuprofen (0.05%). NO is synthesized by the enzyme nitric oxide synthase (NOS) (25). NOS exists in three isoforms, neuronal (nNOS), inducible (iNOS) and endothelial nitric oxide synthase (eNOS), and the iNOS isoform is predominantly responsible for NO production in articular cartilage (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, histopathlogical examination of the arthritic joints revealed that FG (1%) more markedly suppressed the articular lesions than ibuprofen (0.05%). NO is synthesized by the enzyme nitric oxide synthase (NOS) (25). NOS exists in three isoforms, neuronal (nNOS), inducible (iNOS) and endothelial nitric oxide synthase (eNOS), and the iNOS isoform is predominantly responsible for NO production in articular cartilage (25).…”
Section: Discussionmentioning
confidence: 99%
“…NO is synthesized by the enzyme nitric oxide synthase (NOS) (25). NOS exists in three isoforms, neuronal (nNOS), inducible (iNOS) and endothelial nitric oxide synthase (eNOS), and the iNOS isoform is predominantly responsible for NO production in articular cartilage (25). It is well known that NO produced by cartilage and synovial cells is implicated in the pathogenesis of human osteoarthritis and rheumatoid arthritis (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…3,7 Under static conditions, nutrient transfer is governed by diffusion, that is, transport driven by a concentration gradient. However, diffusive transport is relatively slow (e.g., Fermor et al 8 reported diffusivities of approximately 2.5Â10 À7 cm 2 s À1 for uncharged dextrans in the surface zone of cartilage) and generally accounts for supplying cells at a depth of only a few hundred micrometers from the surface within a reasonable time. 9 In particular, for articular cartilage, which lacks a vascular bed, the notion arose that a pumping action due to joint mobility could contribute to cartilage nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Measured oxygen tension in articular cartilage ranges from 7% (53 mm Hg) in the superficial layer to less than 1% (7.6 mm Hg) in the deep zone [72,73] of the oxygen tension of synovial fluid.…”
Section: Nutrients/o2 Gradientmentioning
confidence: 99%